Synthesis and evaluation of NLRP3-inhibitory sulfonylurea [11C]MCC950 in healthy animals. Issue 12 (15th June 2020) - Hill, James R.; Shao, Xia; Massey, Nicholas L.; Stauff, Jenelle; Sherman, Phillip S.; Robertson, Avril A.B.; Scott, Peter J.H.
Graphical abstract: Abstract: The diaryl sulfonylurea MCC950/CRID3 is a potent NLRP3 inhibitor (IC50 = 8 nM) and, in animal models, MCC950 protects against numerous NLRP3-related neurodegenerative disorders. To evaluate the brain uptake and investigate target engagement of MCC950, we synthesised [ 11 C-urea]MCC950 via carrier added [ 11 C]CO2 fixation chemistry (activity yield = 237 MBq; radiochemical purity >99%; molar activity = 7 GBq/µmol; radiochemical yield (decay-corrected from [ 11 C]CO2 ) = 1.1%; synthesis time from end-of-bombardment = 31 min; radiochemically stable for >1 h). Despite preclinical efficacy in neurodegeneration studies, preclinical positron emission tomography (PET) imaging studies in mouse, rat and rhesus monkey revealed poor brain uptake of low molar activity [ 11 C]MCC950 and rapid washout. In silico prediction tools suggest efflux transporter liabilities for MCC950 at microdoses, and this information should be taken into account when developing next generation NLRP3 inhibitors and/or PET radiotracers.